A Simple and Swift Method for Isolating High Quality RNA from Jute (Corchorus spp.) - Mahmood, Niaz; Ahmed, Razib; Azam, Muhammad Shafiul; Khan, Haseena (Plant Tissue Culture and Biotechnology, 2011)
High quality RNA extraction is a prerequisite for various types of genetic analyses. Many a time, the existing RNA isolation methods and commercial kits are either time consuming or fail to isolate high quality RNA from plants rich in polysaccharides, oil and other secondary metabolites since different plants contain different amounts of nucleic acids (Khan et al. 2004, Loomis 1974). This problem is particularly acute in case of jute (Corchorus spp.), which is rich in mucilage and other polysaccharides that tends to interfere with the downstream processes (Kundu et al. 2011, Pandey et al. 1996). Several guanidium salt based methods have been successful for RNA isolation from jute seedlings (Khan et al. 2004), but are often cumbersome and expensive; hence limit simultaneous processing of large number of samples. Here we report a simplified and swift protocol for isolating high quality RNA from jute by making key modifications in tissue denaturation and precipitation steps in the protocol described by Ghawana et al. (2011). The protocol allows consistent production of high quality RNA from different species, which makes it particularly suitable for comparative plant genome research. The extraction time has been reduced from two days (for standard guanidium-acid-phenol extraction protocols) to about one hour and the extracted RNA was suitable for downstream processes like cDNA synthesis and expression pattern analysis. Key words: Jute, Corchorus spp., Swift method, RNA isolation, RT-PCR D. O. I. 10.3329/ptcb.v21i2.10244 Plant Tissue Cult. & Biotech. 21(2): 207-211, 2011 (December) - Short communication